Multi-local settlement mobilities. Issue 15 (17th September 2020) - Boese, Martina; Moran, Anthony; Mallman, Mark
ABSTRACT : Policy and recent scholarly understandings of settlement have both neglected continued movements of international migrants post-arrival in their destination country. The concept of settlement appears tied to outdated sedentary social science approaches that recent mobilities scholarship challenges. Rather than contrasting internal movements with settlement, we argue settlement is better understood as a social process involving spatial movement as well as stasis. The conceptual value of settlement can be enhanced by understanding it as entailing temporally, relationally, and politically bound practices of spatial mobility and immobility. These settlement mobilities are long-term processes often involving multiple localities. Drawing on a qualitative study of international migrants and key stakeholders residing in and near a rural town in South Eastern Australia, we examine how multiple moves are a regular part of post-migration journeys of settlement. While settlement already includes core concerns with new arrivals' establishment of employment, family, and place-based community, our findings show that those with migrant and refugee backgrounds experience these multi-locally, as intersecting factors in decision-making and practices of moving between cities and rural areas.